Electrometallurgical Relationships In Electric Smelting Furnaces - J. Persson; N. G. Bliss (The Southern African Institute of Mining and Metallurgy, 2004)
Electric furnaces used for smelting and those used for scrap melting exhibit different performance profiles in terms of electrical characteristics. However, the underlying principles are the same for either case. The rationalization of these variables is a major concern for furnace operators and designers. This paper presents the results of a two year study of high speed real time data from a number of electric furnaces around the world, covering a very wide range of design philosophy and product manufacture, to provide a better mathematical insight into rationalizing the furnace operation.